Evaluation of the compactive effort on the stripping characteristic of hot mix asphalt (HMA) mixtures - Subramaniam, Suthagaran (2006)
Generally, moisture susceptibility is a HMA mixture’s tendency towards stripping. To combat moisture susceptibility, proper mix design is essential. However if a mix is properly designed but not compacted sufficiently it could be also subjected to stripping. This study is to evaluate the relationship between different compactive efforts on stripping, as well as to suggest the most appropriate indicative test to envisage the stripping characteristic in HMA mixtures. Two test methods were carried out to assess the stripping, which are quantitative strength test for compacted specimens and qualitative test for loose uncompacted specimens. Samples compacted with 35, 50 and 75 blows of Marshall hammer were used to determine the stripping in HMA. For the quantitative test, moisture induce damage test (AASTHO T 283) is utilized to forecast the stripping while for qualitative test, Coating and Stripping of Bitumen-Aggregate Mixtures (ASTM D1664-80) and Effect of Water Bituminous-Coated Aggregate Using Boiling Water (ASTM 3625- 91) were used. The results show that increase in compactive effort would decrease the optimum asphalt content. In the moisture induce damage test, those 35 blows and 50 blows have larger TSR value, which the 35 blows is 24% and 50 blows is 14% higher than 75 blows. Similarly, the loose uncompacted specimens indicate that both of these lower blows have lesser stripping potential. This shows that, the lower the blow the larger optimum asphalt content thus decreases the stripping potential of the HMA. Besides that, it was also found that moisture induce damage test is a more appropriate method to use in evaluating of stripping characteristic of HMA.